Reviewing elements of feminism in a Malaysian play: Kuala Lumpur knock-out - Ahmad Kamal, Basyah Sallehuddin; Rosdeen, Suboh (UNIMAS Publisher, 2018)
Kuala Lumpur Knock-Out(henceforth to be known as “KL-KO”) is the second project of Kuali Works. KL-KO is the most commercial performance staged by Kuali Works; this was the first time Kuali Works advertised its play in mainstream newspapers in the, as well as solid patronages from an impressive list of sponsors. Written and directed by Ann Lee, it was staged in Experimental Theatre, Kuala Lumpur in 1996. KL-KO revolves around the life of Tan Ai Leng (played by critically acclaimed dancer Mew Chang Tsing), a young Chinese woman from Penang who dreams of fighting Mike Tyson in an exhibition-boxing match in Kuala Lumpur. Simultaneously, her best friend Mazuri experience a rather unpleasant incid ent at her workplace. After 22 years, it is recompensing to look back at the relevance of the issues highlighted in this play. Simultaneously, one would realise that the elements of feminism discussed in this play are the real problems faced by women in this country, even after the new millennium.